Peran Fasilitas Pendukung Terhadap Kepuasan Wisatawan di Wisata Sapatapaan Kabupaten Sumedang - Renaza Salsabila; Oman Sukirman; ⁠Irena Novarlia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Destinations with the concept of ecotourism are natural attractions that still maintain their culture but are not outdated. Has an attraction that has the potential to bring in tourists, but is not yet well known enough to the outside community, one of which is the Sapatapaan tourist destination in Sumedang Regency. This study aims to analyze the role of tourism support facilities on tourist satisfaction in Sapatapaan tourist destinations. The research method used in this research is quantitative research method with descriptive and verification data analysis techniques. The data collection technique was carried out by distributing questionnaires to 100 respondents who were tourists who had visited Sapatapaan tourist destinations. The data that has been collected will be analyzed using the simple linear regression analysis method and using IBM SPSS Statistic 26 software. The results showed that supporting facilities have a significant positive impact on the level of tourist satisfaction.